Variations in tocopherol, tocotrienol, avenanthramide and saponin content in oats and the influence of milling and baking processes - Pöysä, Marjo; Pihlava, Juha-Matti; Fedotov, Anna; Lampi, Anna-Maija; Hietaniemi, Veli; Piironen, Vieno (Academic Press, 2024)
Oats, as whole-grain cereal, are a good source of nutrients, including compounds located in the outer layers of groats, such as fibre and bioactive compounds. The aim was to study variations in selected bioactive compounds of oats and evaluate possible losses due to oats' milling into flour and the baking process. The levels of tocopherols and tocotrienols (i.e. tocols), avenanthramides and saponins of 30 Finnish-grown oat batches representing different cultivars were measured. The analysed sample materials were laboratory hulled non-heated groats, flours from a commercial mill and breads. The oat batches showed marked variation, and the greatest variation among the batches was observed in avenanthramide content, with a 10-fold difference. Meanwhile, the variation in tocols and saponins was approximately twofold. As a result of the change from groats to flours, the content of tocols, avenanthramides and saponins decreased by 1–40%, usually 1–33% and 1–57% in the oat batches, respectively. Losses in avenanthramides and saponins were also observed after baking. Avenanthramides seemed to tolerate the studied processing steps the best. This study showed that the oat batches’ losses in the studied bioactive compounds differed due to multiple factors such as physical separation and chemical reactions.
Keywords: oats; tocols; avenanthramides; saponins